Impact of early intervention on comprehensive language and academic achievement in Japanese hearing-impaired children with cochlear implants. Issue 12 (December 2015) - Sugaya, Akiko; Fukushima, Kunihiro; Kasai, Norio; Kataoka, Yuko; Maeda, Yukihide; Nagayasu, Rie; Toida, Naomi; Ohmori, Shyuhei; Fujiyoshi, Akie; Taguchi, Tomoko; Omichi, Ryotaro; Nishizaki, Kazunori
Abstract: Objectives: Early hearing detection and intervention (EHDI) is critical for achievement of age-appropriate speech perception and language development in hearing-impaired children. It has been 15 years since newborn hearing screening (NHS) was introduced in Japan, and its effectiveness for language development in hearing-impaired children has been extensively studied. Moreover, after over 20 years of cochlear implantation in Japan, many of the prelingual cochlear implant (CI) users have reached school age, and the effect of CI on language development have also been assessed. To identify prognostic factors for language development, audiological/language test scores and demographic factors were compared among prelingual severe-to-profound hearing-impaired children with CI divided into subgroups according to age at first hearing aid (HA) use and whether they received NHS. Methods: Prelingual severe-to-profound deafened children from the Research on Sensory and Communicative Disorders (RSCD) project who met the inclusion criteria were divided into groups according to the age (in months) of HA commencement (before 6 months: group A, after 7 months: group B), and the presence or absence of NHS (groups C and D). Language development and socio-economic data were obtained from audiological/language tests and a questionnaire completed by caregivers, respectively. Results: In total, 210 children from the RSCD project participated in this study. Group A ( n  = 49) showed significantly higher scores on comprehensive vocabulary and academic achievement ( p  < 0.05) than group B ( n  = 161), with no difference in demographics except for significantly older age in group B. No differences in language scores were observed between group C ( n  = 71) and group D ( n  = 129), although participants of group D was significantly older and had used CIs longer ( p  < 0.05). Conclusions: Early use of HAs until the CI operation may result in better language perception and academic achievement among CI users with prelingual deafness. A long-term follow-up is required to assess the usefulness of NHS for language development.